Endoscopic Anatomy of Persistent Trigeminal Artery: A Cadaveric Study - Komatsu, F.; Komatsu, M.; Di Ieva, A.; Tschabitscher, M. (min - Minimally Invasive Neurosurgery, 2011)
Persistent trigeminal artery (PTA) is one of the carotid-basilar anastomoses and occasionally complicates vascular or neoplastic pathology. The aim of this study was to become more familiar with the anatomy associated with PTA using an endoscopic view.PTA was incidentally encountered in a fresh cadaver. Purely endoscopic approaches via supraorbital (extradural and intradural routes), endonasal, and retrosigmoid routes were performed with 4-mm, 0- and 30-degree rigid endoscopes.The PTA belonged to Salas’s lateral type and Saltzman’s type 1. The supraorbital extradural approach allowed good visualization of the origin and the cavernous portion of the PTA through the infratrochlear triangle. Using the endonasal route, the cisternal portion of the PTA and its confluence to the basilar artery were demonstrated after opening the clival dura; however, the origin of the PTA and the cavernous portion of the PTA were not sufficiently exposed even using a direct approach to the cavernous sinus. The retrosigmoid approach revealed the anatomical relationship among the PTA, trigeminal nerve, and abducent nerve in the petroclival region.These 3 endoscopic approaches provided a superb image of the PTA and contribute to the anatomical comprehension of PTA. Additionally, these approaches make us more familiar with an endoscopic view of PTA.
Keywords: endonasal approach; endoscopy; persistent trigeminal artery; retrosigmoid approach; supraorbital approach